Effects Of Women’s Seductive Dressing On Men’s Behaviour And Judgement: A Study In Selected Universities In Ghana - Anku, Joycelyn; Danso, Daniel Kwabena; Kuwornu-Adjaottor, Jonathan E.T. (Advances in Social Sciences Research Journal, 2018)
Fashion, nowadays among others, has ostensibly been a defining factor of class differentiation among university students. Most students, particularly the females, struggle daily to meet up to these standards. Whereas modesty, courtesy, virtue and chastity among others are the terms which characterised the dressing of parents in a decade ago, modernity seems to have swept all these away and recast them in new relative meanings. In the light of this the study sought to find out the effects of women’s suggestive dressing on men’s behaviour and judgement. The study adopted survey as a research design. The study population involved students from University of Education, Winneba (Kumasi campus), Kwame Nkrumah University of Science and Technology, University of Ghana, Ghana Telecommunication University College and University of Development Studies. A sample size of 250 students was considered for the study. The constituents were made up of 125 females whereas the males were 125. Stratified sampling technique was used to group the population into sub strata. However, simple random sampling was used to select the five (5) universities. The study used questionnaire as the data collection instruments. The study found that there are different attires worn by female students on university campuses. Aside these varieties of dresses lay the motives for which female students wear them that culminates into the different attitudes men put up towards them. That is to say, most male students get tempted to lust after female students by their dressings. This affinity has the possibility of leading to promiscuous lifestyle on campuses. Based on this conclusions were made and recommendations included the issue that there should be institution of control measures on the university campuses to help monitor and direct females students to dress well.